Flipbook dan Wordwall dalam Pembelajaran matematika di SMP Muhammadiyah Al-Amin Kota Sorong - Trisnawati, Nika Fetria; Situmorang, Helena (Kilau Publishing, 2025)
Mathematics learning at the junior high school level is often perceived as difficult and boring, particularly in the topic of integers, resulting in low student learning outcomes and motivation. This condition is influenced by teacher-centered instructional approaches and the limited use of interactive learning media. This community service activity aimed to improve students’ learning outcomes and motivation using digital flipbooks, Wordwall, and simulated buying and selling transactions using play money for seventh-grade students at SMP Muhammadiyah Al-Amin, Sorong City. The method adopted a development and empowerment approach through the design of learning media, the implementation of discovery-based learning, and evaluation using pre-test and post-test. The activity was conducted in three meetings involving 20 students. The results showed an increase in learning mastery from 15% in the pre-test to 80% in the post-test, accompanied by improvements in students’ motivation, engagement, and positive attitudes toward mathematics learning. These findings confirm the effectiveness of interactive media in creating meaningful and enjoyable learning experiences.